CONCEPTUALIZING TERTIARY EDUCATION MOTIVATION: A MULTIMEDIA INSTRUCTIONAL VIDEO APPROACH HARNESSING UiTM ZAKAT SERVICES - Siti Sarina Sulaiman; Noorfaizalfarid Mohd Noor; Nadia Abdul Wahab; Afiffudin Mohammed Noor; Mohammad Hafiz Ismail (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
This research demonstrates a Community Services Responsibility (CSR) initiative that utilises instructional videos as an interactive tool for knowledge dissemination. It aims to improve Universiti Teknologi MARA (UiTM) Perlis branch students’ and potential future UiTM students’ awareness regarding the Zakat financial assistance offered by Universiti Teknologi MARA (UiTM) Malaysia. This is also an effort to provide the necessary motivation to encourage school students to aim for tertiary education. The study involves two groups: newly enrolled students at the UiTM Perlis branch and upper secondary school students from selected schools around Perlis, Malaysia. These students will explore the specifically designed multimedia instructional video regarding Zakat accommodations. This video is carefully designed to ensure audience engagement and understanding. The research employs a Quasi-Experimental Research Design with pre-test and post-test assessments to evaluate the effectiveness of the instructional videos. Overall, the study has produced a compelling video that can provide understanding and assistance in accessing the Zakat services in UiTM while at the same time promoting social responsibility towards the country’s future educated generation.